Hydrochemistry and stable isotopes (δ18O and δ2H) tools applied to the study of karst aquifers in southern mediterranean basin (Teboursouk area, NW Tunisia). (January 2018) - Ayadi, Yosra; Mokadem, Naziha; Besser, Houda; Khelifi, Faten; Harabi, Samia; Hamad, Amor; Boyce, Adrian; Laouar, Rabah; Hamed, Younes
Abstract: Karst aquifers receive increasing attention in Mediterranean countries as they provide large supplies water used for drinkable and irrigation purposes as well as for electricity production. In Teboursouk basin, Northwestern Tunisia, characterized by a typical karst landscape, the water hosted in the carbonates aquifers provides large parts of water supply for drinkable water and agriculture purposes. Groundwater circulation in karst aquifers is characterized by short residence time and low water-rock interaction caused by high karstification processes in the study area. Ion exchange process, rock dissolution and rainfall infiltration are the principal factors of water mineralization and spatial distribution of groundwater chemistry. The present work attempted to study karstic groundwater in Teboursouk region using hydrochemistry and stable isotopes (δ 18 O and δ 2 H) tools. Karst aquifers have good water quality with low salinity levels expressed by TDS values largely below 1.5 g/l with Ca-SO4 -Cl water type prevailing in the study area. The aquifers have been recharged by rainfall originating from a mixture of Atlantic and Mediterranean vapor masses. Highlights: Hydro and isotope geochemistry were used in this study: To identify the hydrodynamic functioning of the karst aquifer; To investigate the water type of groundwater in the semi-arid north-western Tunisia;